Retention of amylase in the secretory granules of parotid gland after extensive release of Ca++ by ionophore A-23187 (The Rockefeller University Press, 1977)
The effect of the ionophore A-23187 was tested on isolated secretory granules of rat parotid gland. The ionophore caused extensive release of calcium from the granules without effecting release of amylase or other secretory proteins. It is therefore concluded that the role of calcium in the granules is probably not that of a stabilizing agent.